(3EeOGO GdaJGM TQM fhQ GdEjVGM hfLGI GdCQhGMs - (3GdoqToQrfoHdGdj GdeUQj, MSf Hf YeGQ Hf Ydj, (B1069 (3g`s ((3YKeGf Hf QVhGf GdLQeGfjs)
(3ChdgG (B:s
(3HYO GdHSedI ; (B[ (3GdMeO ddg GdPj Ndb cd TjA HbOQJg hChLOgs
(3BNQgG (B:s
(3hgPG eG JjSQ LeYg ef GdTQM cGdeJf ddYGLR GdMbjQ hde jcf EdG HYfGjI ehdGg Gdbhj GdbOjQ GdMeO ddg GdPj gOGfG dgPG heG cfG dfgJOj dhdG Cf gOGfG Gddg hUdi Gddg Ydi SjOfG hehdGfG eMeO NGJe CfHjGAgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 208s
(3GdCYdGe (B1 / 575s
(3EjVGM Gdecfhf (B1 / 126s
(3gOjI GdYGQajf (B1 / 292s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs